Progress of pulmonary hypertension and high manganese levels through congenital portosystemic shunt closure. Issue 9 (12th September 2022) - Kakiuchi, Toshihiko; Baba, Yuta; Minematsu, Nobuya; Doi, Hirohito; Kumamoto, Takashi
Abstract: A 6‐year‐old girl with congenital portosystemic shunt presented with abnormal manganese levels and improving pulmonary hypertension even 1 year after shunt vascular ligation. As the progress after portal vein blood flow recovery varies among individuals, long‐term follow‐up of patients with congenital portosystemic shunt is needed. Abstract : A 6‐year‐old girl with congenital portosystemic shunt presented with abnormal manganese levels and improving pulmonary hypertension even 1 year after shunt vascular ligation. As the progress after portal vein blood flow recovery varies among individuals, long‐term follow‐up of patients with congenital portosystemic shunt is needed.